ENDOCRINE DISRUPTORS, ESTROGENIC ACTIVITY BY THE YES BIOASSAY AND ACUTE TOXICITY IN SOUTHEASTERN BRAZIL METROPOLITAN SURFACE WATERS - Teresa Lima do Nascimento, Marilia; de Oliveira Santos, Ana Dalva; Cunha, Danieli; Cruz Felix, Louise; Gomes, Giselle; Marclei Arruda Rangel, Carlos; Ann Hauser-Davis, Rachel; Monteiro da Fonseca, Estefan; Maia Bila, Daniele; Baptista Neto, José Antônio (Geochimica Brasiliensis, 2022)
This study aimed to determine endocrine disruptors in urbanized rivers Maracanã and Mangue Channel in Rio de Janeiro the second most populated city in Brazil. Bisphenol A, 17β-estradiol, estriol, and 17α-ethinylestradiol were determined by high-performance liquid chromatography with a diode array detector and fluorescence detector In addition, the evaluation of estrogenic activity was performed by the YES bioassay (Yeast estrogen screen) with the Saccharomyces cerevisiae yeast, and acute toxicity assays were performed using Daphnia similis and Vibrio fischeri. Estrogenic activity in the water samples ranged from below the limit of detection (<LD) to 1.6 ng L-1, while bisphenol A ranged from 22.3 to 1325.2 ng L-1 and estrogens 17β-estradiol from <LD to 55.2 ng L-1, estriol from <LD to 313.7 ng L-1 and 17α-ethinylestradiol, from <LD to 409.4 ng L-1. The acute toxicity was not detected in both analyzed organisms. The present study indicates a serious level of pollution by the compounds evaluated with significant risks to the aquatic ecosystem, mainly for Guanabara Bay which receives urbanized river discharge. Therefore, recommending the need for systematic monitoring and mitigating actions in these water bodies.